Millisecond studies of secretion in single rat pituitary cells stimulated by flash photolysis of caged Ca2+. - Thomas, P (1993)
To study the final steps in the secretory pathway of rat pituitary melanotrophs, we have monitored changes in cell surface area due to exocytosis after flash photolysis of caged Ca2+. A step increase in cytosolic [Ca2+] to 45-125 microM triggers three phases of exocytic secretion. A small cohort of a few hundred vesicles is exocytosed in 40 ms in a secretory burst with a peak rate of 17,000 vesicles/s. Next, 2700 more vesicles are released in a slower phase that is complete within 400-1000 ms. Finally, vesicles continue to be released slowly (500 vesicles/s) for > 8s. The approach described provides a way to identify and monitor the final steps in the secretory pathway at millisecond resolution. That a small portion of secretory vesicles can be released much faster than all others suggests that these vesicles are functionally equivalent to those at the presynaptic active zone of a neuron. Their release would be fast enough to be temporally correlated with single action potentials.